Near-Road Traffic Emission Dispersion Model: Traffic-Induced Turbulence Kinetic Energy (TKE) Measurement - Zhice Hu; Kenneth E. Noll (Atmosphere, 2023)
This article delineates the characterization of traffic-induced turbulent kinetic energy (TKE) in areas proximate to roadways using real-world traffic conditions. Traffic-induced TKE serves as a pivotal tool to refine the parameters of eddy diffusivity within air dispersion modeling, thereby facilitating a more accurate representation of near-road model-estimated traffic emission with TKE-related traffic conditions. Six hundred observations facilitated the detailed TKE characterization, which incorporated a comprehensive assessment of wind speed and traffic conditions, including parameters such as vehicle flow rate, speed, and classifications into categories such as heavy-duty vehicles (HDVs) and light-duty vehicles (LDVs). Five-minute measurement intervals were utilized to pinpoint the substantial variations in TKE generated through traffic flow, particularly highlighting the more chaotic yet swiftly dissipating energy contributions from HDVs. Monitoring was conducted on two urban freeways characterized by markedly different traffic compositions (quantified with HDV%) and distinct road configurations. The TKE derived from traffic over five-minute intervals is correlated with concurrently measured variables such as vehicle flow, speed, and traffic types. The ensemble mean method was utilized to delineate the characteristics of traffic-induced TKE during both steady- and unsteady-state traffic flows, with a focus on traffic density as a key parameter. The results reveal different trends in the behavior of traffic induced TKE. The substantial impact of HDV-induced TKE was quantified using a comparative analysis of normalized traffic-induced TKEs between HDVs and LDVs. This analysis demonstrates that the influence exerted by a single HDV is approximately eleven times that of a single LDV in close proximity to road locations. Within the traffic fleet, HDVs constitute only a minor fraction, typically amounting to 1 to 10% of the total vehicle flow rate. However, their considerable impact and positive correlation with traffic induced TKE was evaluated using a detailed analysis of LDV flow subdivisions.